EFEKTIVITAS PENYULUHAN TERHADAP PENGETAHUAN, SIKAP DAN NIAT REMAJA PUTRI UNTUK MENGKONSUMSI TABLET TAMBAH DARAH - Era Revika; Retno Heru Setyorini; Fitriani Mediastuti (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2025)
Anemia is a health problem in adolescent girls.  The prevalence of anemia among young women risks disrupting growth, development and quality of life. One of the recommended efforts to prevent anemia is to consume blood supplement tablets (TTD). Counseling is one method of increasing knowledge and changing attitudes. This research aims to analyze the effectiveness of counseling on the knowledge, attitudes and intentions of young women in consuming tablets. add blood. Counseling was carried out to increase knowledge of young women regarding the importance of consuming TTD in preventing anemia. The method used is experimental research with a pre-test post-test design. The research sample consisted of high school and vocational school teenagers. Data was collected through questionnaires that measured teenagers' knowledge, attitudes and intentions before and after counseling. The results of the study prove that providing intervention is statistically effective in increasing knowledge, attitudes and intentions regarding the benefits of blood supplement tablets. This research concludes that counseling is effective in increasing teenagers' knowledge, attitudes and intentions towards consuming TTD, which is expected to reduce the prevalence of anemia in young women in Indonesia